Positive or negative correlation between actual and potential evaporation? Evaluating using a nonlinear complementary relationship model. Issue 2 (18th February 2014) - Han, Songjun; Tian, Fuqiang; Hu, Heping
Abstract: Understanding whether a positive or negative correlation between actual ( E ) and potential ( Ep ) evaporation is of great importance in detecting changes of E from Ep . In this study, such correlation was evaluated via the linear regression slope ( k ) between E and Ep derived from a nonlinear complementary relationship model. k varies with the relative degree of variability in the radiation term ( Erad ) and aerodynamic term ( Eaero ) of Ep, and is further affected by water availability. The sign of k is always positive under conditions with high Erad variability but at the same time with low Eaero variability (commonly true on an hourly basis). Under conditions with high Eaero variability but at the same time with low Erad variability, the sign of k tends to change from negative to positive with more readily water availability. On a daily or annual basis, the sign of k would be related with water availability. Under water‐limited conditions, the Eaero variability is more significant than the Erad variability, and negative k is expected. Under energy‐limited conditions, the Erad variability is compared to or even much obvious than the Eaero variability, and positive k is expected. This implies a negative correlation between E and Ep under water‐limited conditions but a positive correlation under energy‐limited conditions on the daily or annual basis. The above analysis is confirmed in a grassland site in Northeast China at daily and half‐hourly time scales. The correlation between annual E and Ep over China was evaluated using data of 690 meteorological stations from 1956 to 2005. The k values change from negative in arid regions to positive in humid regions. According to k and the decreasing trends in annual Ep, it is deduced that E increased for most stations in arid regions but decreased for most stations in humid regions. Key Points: Evaluating correlation between E and Ep via complementary relationship model Variability in Erad and Eaero, and wetness affect correlation between E and Ep Negative correlation in arid regions, but positive in humid regions in China